Effects of polymeric materials on bacterial aggregation and quorum sensing - Sui, Cheng (2017)
In order to develop novel antibacterial therapies that combine anti-adhesion, anti-quorum sensing and the delivery of conventional antibiotics, the effects of polymers on bacterial aggregation and quorum sensing (QS) were studied. QS is a term used to describe method by which bacteria use chemical signal molecules to modulate pre-infection behaviour such as surface attachment. Polymers that can interfere with bacterial adhesion or the signal molecules used for QS are therefore a potential means to control bacterial population responses. In this thesis, the ability of the cationic polymers poly (N-[3-(dimethylamino) propyl] methacrylamide) (p(DMAPMAm), P1) and poly (N-dopamine methacrylamide-co-N-[3-(dimethylamino) propyl] methacrylamide) (p(DMAm-co-DMAPMAm), P2) to cluster a range of bacteria, such as Staphylococcus aureus(Gram-positive), Vibrio harveyi, Escherichia coli and Pseudomonas aeruginosa(Gram-negative) under conditions of varying pH and polymer concentration was investigated. It was identified that clustering ability was strongly dependent on the balance between charge and hydrophobicity. The results also suggested that catechol moieties might have a positive effect on adhesive properties. Moreover, the potency of polymers against QS of Vibrio harveyi was assayed via testing bioluminescence. P1 which was able to bind to the surface of bacteria through electrostatic interactions enhanced the expression of QS and P2 which could bind to both the bacteria and QS signals showed the ability to both enhance and reduce light production. Furthermore, polymeric vesicles made of copolymers containing poly (3,4-dihydroxy-L-phenylalanine methacrylamide) (p(L-DMAm)) which displayed similar dual affinity compared toP2 were prepared and their ability to modulate QS responses in Vibrio harveyi was demonstrated. All the vesicles showed higher potency in quenching bioluminescence than their linear polymer analogues. To explore the feasibility of using self-assembled polymers for anti-microbial drug delivery, silver loaded DOPG lipid vesicles were made and were found to interfere with QSwhile reducing bacterial viability when the concentration of Ag+ was above the MIC (0.1 μg/mL). The results overall suggested that combined antimicrobial therapies might be possible using polymers and both QS and cytostatic or cytotoxic agents.